On Hyperbolic Split Quaternions and Hyperbolic Split Quaternion Matrices - Ozyurt, Gozde; Alagoz, Yasemin (SPRINGER BASEL AG, 2018)
The purpose of this study is to investigate some properties of 2x2 hyperbolic split quaternion matrices. To verify this, we use matrices corresponding to the basis of hyperbolic split quaternions. Moreover, we give 4 x 4 hyperbolic matrix representation and 8 x 8 real matrix representation of a hyperbolic split quaternion.
Keywords: Hyperbolic split quaternion; Hyperbolic split quaternion matrix; Primary 15B33; Secondary 11R52; Mathematics; Physics